The adoption and performance of official facebook fan page (FFP) among global airline companies - Baghirov, Fakhri (2015)
Organizations nowadays are relying on social media marketing for promotion and CRM purposes. Facebook is one of the most significant social media tools, which has been used worldwide. This study investigates the adoption and performance of Facebook fan pages among global airline companies in developed, least developed and developing countries. The Diffusion of Innovations theory has been applied as the underlying theory in this study. Using content analysis technique the data was collected from official FFP of global airlines. Analysis of Variance (ANOVA) and Chi Square were used to test hypotheses. The result shows no significant difference among the global airline companies in developed, least developed and developing countries in FFP adoption. However, the results shows significant difference in terms of performance and timing of adoption of FFP between the developed, least developed and developing countries. Airlines from developed countries adopted FFP three years earlier than developing countries and performed better than airlines from developing and least developed countries. Academically, this study adds on internet and technology implementation literature. For industry, investigating the performance of FFP should make it clear for global airline companies how to implement FFP successfully